EDUKASI MITIGASI BENCANA BERBASIS MASYARAKAT DI DESA KASIMPAR KECAMATAN PETUNGKRIYON KABUPATEN PEKALONGAN - Sudirman; Zaenal Abidin; M. Adin Setyawan (Universitas Sumatera Barat, 2025)
Kasimpar village is part of the Petungkriyono protected forest and is located in the Welo watershed, which is connected to the Sengkarang watershed and has the potential to become a charming ecotourism area. However, this potential makes the area vulnerable to natural disasters, especially landslides and floods during the rainy season. Unfortunately, the level of knowledge and preparedness of the community in dealing with disasters is still relatively low, which can exacerbate the impact of disasters. Landslides and floods that occurred in Kasimpar Village, Petungkriyono Subdistrict, Pekalongan Regency in early 2025 encouraged the community to be early in coping with disasters. This community service aims to increase the capacity of the Kasimpar Village community in dealing with disasters through a community-based disaster mitigation education program. This community service activity was carried out by Real Work Lecture students of UIN K.H. Abdurrahman Wahid Pekalongan and field supervisors and collaborated with BPBD Pekalongan Regency by applying socialization implementation methods including education about disaster mitigation and strategies for forming disaster preparedness volunteer groups. After implementing this community service program, the results showed that the community who participated in disaster mitigation education activities were inspired to form a special team that would be prepared for inauguration as a Disaster Resilient Village (Destana). The community also felt interested during the activities as seen in the enthusiasm in asking questions. This program is expected to become a model for community empowerment in disaster mitigation in other vulnerable areas.